2005
DOI: 10.1590/s1135-57272005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de los modelos SCORE y REGICOR para el cálculo del riesgo cardiovascular en sujetos sin enfermedad cardiovascular atendidos en un centro de salud de Barcelona

Abstract: (2) UI SAP Sants-Montjuïc-Sarrià-Les Corts-Sant Gervasi RESUMEN Fundamento: No se dispone de estudios que hayan comparado SCORE, REGICOR y Framingham. El objetivo de este trabajo es estudiar cómo clasifican el riesgo cardiovascular las funciones REGICOR y SCORE, su correlación y concordancia respecto a Framingham (1998) y si presentan diferencias respecto a los factores de riesgo cardiovascular en los casos de riesgo alto. Métodos:Estudio descriptivo transversal realizado en atención primaria. Se incluyó a 851… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 23 publications
1
11
1
9
Order By: Relevance
“…Comparisons between SCORE and REGICOR did not disclose that one of them might be better than the other in establishing the CV risk in Spanish individuals without rheumatic diseases [33-37]. In the present study, neither mSCORE nor mREGICOR were shown to be effective in the stratification of the CV risk of Spanish RA patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Comparisons between SCORE and REGICOR did not disclose that one of them might be better than the other in establishing the CV risk in Spanish individuals without rheumatic diseases [33-37]. In the present study, neither mSCORE nor mREGICOR were shown to be effective in the stratification of the CV risk of Spanish RA patients.…”
Section: Discussioncontrasting
confidence: 70%
“…9 In Spain, there are only a few studies designed to describe CVR at the population level. [10][11][12][13][14][15][16][17] These studies are either limited by their sample size, or focused on specific groups with at least one of the classical cardiovascular risk factors (CVRF), or performed in specific regions that may not be representative of the entire country. Furthermore, none of these surveys included high-density lipoprotein cholesterol (HDL-C) in the estimation of CVR.…”
Section: Introductionmentioning
confidence: 99%
“…Systolic and diastolic blood pressure (SBP and DBP) were measured twice with validated and calibrated electronic sphygmomanometers after 5 minutes rest. Cardiovascular risk was calculated according to Framingham-Regicor [13,14] predictive equations calibrated for Girona (Spain) and according to the Score [13] project for European population at low risk. Framingham-Regicor risk tables have been adapted and validated with data from the population of Girona (Spain) in the VERIFICA study [14,15].…”
Section: Methodsmentioning
confidence: 99%